2017
DOI: 10.1007/s40261-016-0481-0
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of Sodium Stibogluconate and Paromomycin Combination for the Treatment of Visceral Leishmaniasis in Eastern Africa: Results from a Pharmacovigilance Programme

Abstract: IntroductionIn 2010, WHO recommended a new first-line treatment for visceral leishmaniasis (VL) in Eastern Africa. The new treatment, a combination of intravenous (IV) or intramuscular (IM) sodium stibogluconate (SSG) and IM paromomycin (PM) was an improvement over SSG monotherapy, the previous first-line VL treatment in the region. To monitor the new treatment’s safety and effectiveness in routine clinical practice a pharmacovigilance (PV) programme was developed.MethodsA prospective PV cohort was developed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 31 publications
3
41
1
1
Order By: Relevance
“…In Bangladesh, in combination with MIL or AmBisome, PMM showed efficacy similar to that of AmBisome monotherapy for the treatment of VL (7). A study has shown that combined sodium stibogluconate (SSG) and PMM treatment in Sudan, Kenya, Uganda, and Ethiopia was an effective first-line option for VL chemotherapy (8). A retrospective study on the treatment of post-kala azar dermal leishmaniasis (PKDL), a complication of VL, showed that combination therapy with PMM was more effective than monotherapy with SSG in East Africa (9).…”
mentioning
confidence: 99%
“…In Bangladesh, in combination with MIL or AmBisome, PMM showed efficacy similar to that of AmBisome monotherapy for the treatment of VL (7). A study has shown that combined sodium stibogluconate (SSG) and PMM treatment in Sudan, Kenya, Uganda, and Ethiopia was an effective first-line option for VL chemotherapy (8). A retrospective study on the treatment of post-kala azar dermal leishmaniasis (PKDL), a complication of VL, showed that combination therapy with PMM was more effective than monotherapy with SSG in East Africa (9).…”
mentioning
confidence: 99%
“…The SSG-PM combination is the first choice in the region (1), with an efficacy of 91% at 6 months, but it requires 17 days of hospitalization (46). Effectiveness data showed that this regimen is more toxic and results in greater mortality in patients Ͼ50 years old and in coinfected HIV-VL patients (47). Trained health personnel and upgraded hospitals are key to minimizing the limitations of this regimen until a new (ideally oral) combination is ready.…”
Section: Discussionmentioning
confidence: 99%
“…A pharmacovigilance program in which 3,126 VL patients were treated with SSG-PM in 12 facilities in Ethiopia, Kenya, Sudan, and Uganda has confirmed no new safety signals, a high effectiveness at the EoT (95.1%), and a low mortality of 0.9%. However, results from this program also showed that SSG-PM is not a suitable treatment for patients who are Ͼ50 years old and HIV-VLcoinfected patients due to its lower efficacy and higher mortality rate, although these represent a small proportion of all VL patients (47). In Sudan, MSF found that the efficacy of SSG-PM treatment was 86% (506/591) at 6 months.…”
Section: Successes and Pitfalls Anthroponotic Visceral Leishmaniasismentioning
confidence: 97%
“…Current control measures that include case detection, drug treatment, and insecticide-impregnated bed nets are failing as evidenced by repeated epidemics especially in East Africa. In addition, increasing drug resistance and geographical expansion of the leishmaniases due to global warming and wars make the search for vaccines for the leishmaniases a necessity [2,[10][11][12][13][14][15]].…”
Section: Introductionmentioning
confidence: 99%